THE HABITUATION METHOD AS A MEDIUM FOR CHARACTER FORMATION IN ISLAMIC EDUCATION - Rudini, Rudini; Ruhimat, Imat; Jufri, Jufri; Supriatna, Yusup; Sadarela, Sadarela (Universitas Pendidikan Indonesia, 2025)
This study aims to describe the implementation of the habituation method as an effective medium for developing students’ Islamic character. This research employs a descriptive qualitative approach by examining various relevant literature sources, such as books, journals, and educational documents. The findings indicate that the habituation method functions not only as a learning strategy but also as a process of internalizing moral, spiritual, and disciplinary values. This process involves consistency, teacher exemplification, and a supportive school environment. Thus, the habituation method can serve as an effective means of shaping a holistic Islamic character, encompassing aspects of faith, worship, and morality.